Dynamics of learner affective development in early FLL - Mihaljević-Djigunović, Jelena (Array, 2012)
Affective learner factors were first considered as a cause of success in language learning. This was followed by a change in approach and recently authors (e.g., Edelenbos, Johnstone, & Kubanek, 2006) have considered them an important outcome, especially in early foreign language learning (FLL). Current research into affective learner factors in early FLL tries to catch the developmental aspects too, and studies are emerging that take a contextual view as well. This paper describes a study on affective characteristics of young FL learners that combines the developmental and contextual perspectives. Using the case study methodology the author analyses the affective profiles of three young learners of English as a foreign language who were followed for 4 years. The analyses are done taking into account their immediate language learning environment, home support, out-of-school exposure to English and language achievement. The findings suggest that affective learner factors contribute to the dynamic complexity of early FLL.